The least squares solution for nonlinear parameter estimation, with a specific application to a satellite orbiting the earth - Oosthuizen, Joyce (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.